2022
DOI: 10.1097/naq.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Nursing Profession Postpandemic Through Reconstructed Leadership Practices

Abstract: Responding to and navigating the COVID-19 pandemic were demanding and all-consuming for executive nurse leaders. Long-term pandemic challenges will continue and therefore it is important for nurse leaders to develop their reflective practice to increase role competency, gain wisdom, and advance the profession. The complex postpandemic world requires nurse leaders to show up differently, stop ineffective practices, continue best practices, and implement new ideas to improve performance and outcomes. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(54 reference statements)
0
9
0
1
Order By: Relevance
“…Pandemic nurse leadership literature over the past year has focused on how nurse leaders have had to adapt their styles to manage the numerous challenges. Grubaugh and Bernard (2022) proposed that long-standing pandemic challenges will continue and it is important for nurse leaders to focus on communication, teamwork, professional governance, posttraumatic growth, gratitude, diversity/equity/ inclusion and social determinants of health to lead into the future. A survey of 151 nurse leaders concluded that increasing communication, stress management and high visibility and support were needed to combat escalating damage from the pandemic (Turnipseed & VandeWaa, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pandemic nurse leadership literature over the past year has focused on how nurse leaders have had to adapt their styles to manage the numerous challenges. Grubaugh and Bernard (2022) proposed that long-standing pandemic challenges will continue and it is important for nurse leaders to focus on communication, teamwork, professional governance, posttraumatic growth, gratitude, diversity/equity/ inclusion and social determinants of health to lead into the future. A survey of 151 nurse leaders concluded that increasing communication, stress management and high visibility and support were needed to combat escalating damage from the pandemic (Turnipseed & VandeWaa, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before any further development can be achieved, it could take some years to return to the same level of nursing leadership as before the pandemic. Relational leadership styles, such as transformational and authentic leadership, have previously been dominant styles, and both Feistritzer et al (2022) and Grubaugh and Bernard (2022) suggest that complex relational leadership (CRL) is needed for postpandemic nursing, combining effective leadership with engaged clinical nurses who are accountable for decision‐making. CRL is a leadership model that has been identified as a conceptual foundation for navigating Complex Adaptive Systems (CAS), in which nurses at all levels can function.…”
mentioning
confidence: 99%
“…Visibility and listening are key to communication, being and discussing with nursing staff in different spontaneous and organized meetings gives important information what is working well and eliminates rumours and misunderstandings. Encouraging, listening and welcoming contributions creates trust, openness and respect (Grubaugh & Bernard, 2022; Turnipseed & VandeWaa, 2022). While it is possible to participate in traditional shared governance, focusing on responsibility, where nurses and managers share locally based decisions, Grubaugh and Bernard (2022) suggest there is a need to move on and progress to true professional governance.…”
mentioning
confidence: 99%
See 2 more Smart Citations